Fungi associated with sorghum seeds and persistence of Fusarium after surface disinfestation - Velazquez, Pablo Daniel (2026)
Introduction. The distinction between superficial colonization and internal infection by Fusarium spp. in sorghum (Sorghum spp.) seeds is limited when using conventional diagnostic methods, hindering the interpretation of inoculum localization. Objective. To characterize the fungal community associated with commercial sorghum seeds and to evaluate the persistence of Fusarium spp. after surface disinfestation as an indicator of the likely localization of the inoculum. Materials and methods. The study was conducted at the Estación Experimental Agropecuaria Paraná of the Instituto Nacional de Tecnología Agropecuaria, Oro Verde, Entre Ríos, Argentina, between November 2024 and November 2025. Seeds from thirty commercial hybrids were evaluated using a blotter test without surface disinfestation (200 seeds per hybrid). Fungal genera were identified, and their incidence (%) was recorded. Based on Fusarium spp. incidence, twelve sentinel hybrids were selected and subjected to a blotter test with surface disinfestation (2 % NaOCl for 2 min; 100 seeds per hybrid) to assess pathogen persistence. The analysis was descriptive, based on the comparison of incidence before and after treatment. Results. Sixteen fungal genera were identified, with Alternaria, Fusarium, and Cladosporium as the most prevalent. Fusarium spp. showed variation among hybrids, with an incidence range of 0-78 % in the evaluation without disinfestation. In sentinel hybrids, surface disinfestation resulted in variable reductions, with high values in some hybrids, suggesting the removal of mainly superficial inoculum, whereas in others pathogen persistence was observed after treatment. Conclusion. The combination of blotter test and surface disinfestation allowed the characterization of fungi associated with commercial sorghum seeds and the analysis of Fusarium spp. persistence in relation to its likely localization within the seed. Differential patterns among hybrids allowed the interpretation of inoculum origin and highlighted the usefulness of the method for seed health evaluation and preventive management.